A new deep water gastropod of the genus Parabuccinum (Neogastropoda: Buccinulidae) from southwestern Atlantic waters with new data on the distribution of all species - Pastorino, Roberto Santiago Guido (2018)
A new species of the buccinulid genus Parabuccinum Harasewych, Kantor, and Linse, 2000 is described from Southwestern Atlantic deep waters (~54°S, 60°W). Parabuccinum politum sp. n. differs from all other species in the genus in having a smooth shell. Radula, operculum, and soft parts match the other species of the genus. New data on the distribution of all the species of Parabuccinum extends the range of the genus to 37°S in deep waters of the SW Atlantic. Based on present data, only P. bisculptum and P. raucherti were collected outside the Magellanic region to which all the remaining species are confined.